Toxicity of Propylene Glycol Extract of Propolis on Central Nervous System and Liver in Pregnant and Neonatal Rats - Silici, Sibel; Okan, Aslı; Köklü, Betül; Demiray, Sevim; Doğanyiğit, Züleyha (Zeitschrift für Geburtshilfe und Neonatologie, 2023)
Background Propolis has become one of the most preferred supplements due to its beneficial biological properties. Organic (water and vegetable oils) and chemical (ethyl alcohol, propylene glycol, and glycerol) solvents are used for propolis extraction. However, the effects of these chemicals on health should be taken into account.Objectives In this study, the effects of propolis extracts on health were evaluated.Methods 32 pregnant Wistar albino rats and 64 neonatal/young adults were given three different extractions of propolis (propylene glycol, water, and olive oil). Histopathological analyses were performed on the liver and brain, and blood samples were taken from the hearts of rats.Results Histopathological scoring showed that the intensity of pycnotic hepatocyte, sinusoidal dilatation, and bleeding was high in liver samples of pregnant and baby rats given propylene glycol extract of propolis (p<0.05). Propylene glycol extract caused dilatation of blood vessels and apoptosis of neurons in brain tissue. The histopathological score was significantly lower in liver and brain tissues of rats treated with water and olive oil extract compared to propylene propolis groups (p<0.05). Liver enzyme levels in the blood increased in propylene propolis rats (p<0.05).Conclusion Histopathological changes and biochemical alterations may indicate that propylene glycol extracts of propolis are more toxic than olive oil and water extracts. Therefore, olive oil and water extracts of propolis are more reliable than propylene glycol extract in pregnant and infant rats.
Keywords: brain; liver; pregnant rat; propolis; solvent